A Report on Agricultural Insurance in India and the Rise of NAIS (International Journal of Innovative Research in Engineering & Management, 2021)
In general, Crop production is concerned with monsoon  adaptability. As a consequence, promoting different cultures  involves operational risks. Natural disasters have the ability to  impair agricultural production. Crop insurance is simply a  method that may be used to protect against production risks in  farming, and some preparation is needed to conceal any  potential threats. The Indian government has tried with and  worked on creating various crop insurances schemes to meet  this requirement. The National Agricultural Insurance  Corporation of India has been operating the National  Agricultural Insurance Scheme (NAIS) since 2000. All of  these suggestions, however, remained on paper, and the  government's crop insurance policy was not modified. The  aim of this research study is to look at the growth and  development of the national agricultural insurance system, as  well as the key characteristics and advantages of NAIS. As a  consequence, knowledge and proper implementation of the  crop insurance system may assist Indian farmers to increase  food output while reducing the risk of crop failure.
Keywords: Crop Insurance; Insurance System; National Agricultural Insurance; Risk Management